Regional Literature and the Transmission of Culture : Chinese Drum Ballads, 1800-1937 - Wan, Margaret B. (Book collections on Project MUSE., 2020)
"Provides a richly textured picture of cultural transmission in China during the Qing and early Republican eras. Drum ballad texts (guci) evoke one of the most popular performance traditions of their day, opening up surprising new perspectives on vital topics in Chinese literature and history"--Provided by publisher.